Penetapan Kadar Fenol Total dengan Spektrofotometer UV-Vis dan Uji Sitotoksisitas Ekstrak Air Daun Lidah Mertua (Sansevieria masoniana C.) Terhadap Sel Kanker Paru A-549 - Febriyanti, Lilis; Haerussana, Ayu Nala El Muna (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2023)
Cancer is the second most common cause of mortality globally, following cardiovascular disease, according to the World Health Organization (WHO). Leading the list of fatal cancers annually are lung, breast, stomach, liver, and colorectal cancers. Hence, the discovery and development of effective agents to treat various types of cancer is urgently needed. Mother-in-law tongue (Sansevieria masoniana Chahin) leaves contain flavonoids and saponins. However, information regarding the total phenolic content of the aqueous extract of the S. masoniana Chahin leaves is currently unavailable. Hence, this research aims to determine the total phenol content using a UV-Vis spectrophotometer and assess the invitro anticancer activity of the water extract of S. masoniana Chahin through the MTT Assay. From the results of measuring the total phenolic content, the water extract of the leaves contained a phenol content of 3.3061 mgGAE/g. Meanwhile, the results of the cytotoxicity assay on lung cancer cells A-549 showed that the IC50 value of the aqueous extract of S. masoniana Chahin leaves was above 100 ppm, indicating that the extract has less potential as an anti-lung cancer agent.